Effective Approaches in the Transformation of Madrasahs in the Contemporary Era in West Sumatra - Aulia Gusli, Ramadhoni; Aprison, Wedra (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study examines effective approaches to madrasah transformation in West Sumatra, focusing on the challenges faced and development strategies that can be applied. Therefore, the researcher is interested in examining this theme. The approach used is a qualitative method with a case study type of research. Data collection techniques use observation, interviews, and documents from international journals, Scopus, and so on. This research was conducted in madrasahs in West Sumatra. The results show that madrasahs in West Sumatra have shifted from traditional institutions to modern educational institutions, or in other words, they have undergone a transformation. Madrasahs in this region have been trying to transform in the contemporary era. However, they still face obstacles related to the implementation of a curriculum that is not yet fully in line with the needs of the times, challenges in leadership and management, some teachers who use old traditions such as teaching using lecture methods, and inadequate infrastructure.